Kangaroo Market Phenomenon: Identification and Impact on Indonesia’s Economic Growth - Saifullah Fatah; Hardius Usman (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
The stock market holds a crucial role in a country's economy, including Indonesia. As an indicator, the Jakarta Composite Index (JCI) experiences volatility alongside changes in the Indonesian economy. The presence of a kangaroo market in JCI returns can pose a risk of future economic slowdown, making it crucial for monetary authorities to intervene to stabilize the stock market. Therefore, this study identifies the kangaroo market phenomenon, structural economic changes, and the impact of the kangaroo market phenomenon on Indonesia's economic growth. The study focuses on many variables, including JCI returns, kangaroo market, and economic growth from Q3 1995 to Q4 2023. By using the Hodrick-Prescott Filter to define a kangaroo market as JCI returns that lack a deterministic trend, have high volatility, and deviate by one standard deviation from their volatility trend, the results show that most kangaroo phenomena occur during undervaluation. Following the kangaroo market phenomenon, Indonesia's economy underwent five structural changes based on the multiple breakpoint test. Using dynamic linear regression, the overvaluation kangaroo phenomenon negatively affects Indonesia's economic growth, while the undervaluation kangaroo phenomenon has no impact but shows a positive direction.